Vous êtes sur la page 1sur 107

 

R 3

 

 

 

R 3

 

 

 

 

R n

 

 

 

 

 

 

R 2

R 3

 

 

 

 

 

 

 

 

 

 

 

 

R 3

P (2, 1, 1)

v = (2, 3, 1) v = 2 + 3

P 1 (x 1 , y 1 , z 1 ) P 2 (x 2 , y 2 , z 2 )

P 1 P 2

−−→ P 1 P 2

= (x 2 x 1 , y 2 y 1 , z 2 z 1 )

R 3

O XY Z

R 3 O XY Z P ( x, y, z ) O x X y Y

P (x, y, z) O x X y Y z Z

x Y Z x Y Z

y XZ y XZ

z XY z XY

X ( x, 0 , 0) ( x, y 0 , z 0 ) y X (x, 0, 0) (x, y 0 , z 0 ) y 0 z 0 Y Z

Y (0 , y, 0) Y (0, y, 0)

(x 0 , y, z 0 ) x 0 z 0

XZ

Z (0 , 0 , z ) Z (0, 0, z)

(x 0 , y 0 , z) x 0 y 0

XY

Q = {(x, y, z) R 3 /0 x 2; 1 y 3; z 0}

S = [0, 1] × [0, 1] × [0, 1]

P 0 (x 0 , y 0 , z 0 ) R 3 d = (a, b, c)

R 3 L P 0 d −−→

P (x, y, z)

P d

P 0

L = {P (x, y, z)/(x x 0 , y y 0 , z z 0 ) = t(a, b, c); t

R}

L

L :

 

x = x 0 + at

 

y = y 0 + bt

z = z 0 + ct

t R

R 3

R 3 t t ∈ R P 0 ( − 1 , 2 , 4) d

t t R

P 0 (1, 2, 4) d = (2, 0, 2) (3, 1, 1)

d = (1, 0, 1) d = (1, 0, 1) d = (3, 0, 3)

= (1, 0, 0) = (0, 1, 0) = (0, 0, 1)

= 0 x x 0

a

P 0

d = (a, b, c)

a, b, c

= y y 0

b

= z z 0

c

a, b, c

P (1, 2, 3) Q(0, 2, 1)

0 a P 0 d = ( a, b, c ) a, b, c = y

0 a P 0 d = ( a, b, c ) a, b, c = y

0 a P 0 d = ( a, b, c ) a, b, c = y

0 a P 0 d = ( a, b, c ) a, b, c = y

R 3

L 1 :

L 1 :

x

=

x = 6t

=

1 + 2t

2 3t

y

z

= 5 + 4t

y

=

4 4t

z

= 3 2t

t R

t R

L 2 : x 7

3

= y 2

2

L 2 :

x

y

z

=

=

1 + 3u

1 2u

= 1 u

= 1 z

2

u R

(1, 2, 1); (2, 3, 3); (3, 2, 3)

P 0 (x 0 , y 0 , z 0 ) R 3 n = (a, b, c)

R 3 π P 0 n −−→

P (x, y, z)

P 0

P n

π = {P (x, y, z)/(x x 0 , y y 0 , z z 0 ) · (a, b, c) = 0}

∈ π a ( x − x 0 ) + b ( y − y

π a(x x 0 ) + b(y y 0 ) + c(z z 0 ) = 0

P 0 n = (a, b, c)

P

ax + by + cz + d = 0 d P 0

d = 0

P 0 (3, 1, 1)

P 1 (3, 1, 4) P 2 (0, 2, 1)

X

+ cz + d = 0 d P 0 d = 0 P 0 (3 ,

+ cz + d = 0 d P 0 d = 0 P 0 (3 ,

R 3

R 3 π 1 : 2 x − y +3 z = 2 π 2 :

π 1 : 2xy +3z = 2 π 2 : x y z = 0

2x + 4y + 6z 12 = 0

x + z = 1 y + z = 1

L 1 :

x = 1 + 2t

 

y

=

2 3t

z

= 5 + 4t

t R

L 2 : x 7

3

= y 2

2

= 1 z

2

R 3

L 1 :

x = 6t

=

y

4 4t

z

= 3 2t

t R

L 2 :

x

y

z

=

=

1 + 3u

1 2u

= 1 u

u R

L : 2x 1

= 2 y

3

= 4 2z

2

(1, 1, 1)

4

π

π

ax + by + cz + d = 0 P 0 R 3 P 0

d(P 0 , π) = | ax 0 + by 0 + cz 0 + d |

a 2 + b 2 + c 2

−−→

P 0

Q π

Q

−−→

P 0

Q

P 0 π

π

0 + cz 0 + d | √ a 2 + b 2 + c 2

π 1 : 3 x − y + 2 z − 6 = 0 π

π 1 : 3 x − y + 2 z − 6 = 0 π

π 1 : 3 x − y + 2 z − 6 = 0 π

π 1 : 3x y + 2z 6 = 0 π 2 : 6x 2y + 4z + 4 = 0

L :

t R π : 2x + y + 2z + 4 = 0

 

x = 4 + t

 

y = 6 + 8t

z = 7 3t

L

R 3 d P 0 R 3 P 0 L

Q L

−−→

P 0 Q × d

d(P 0 , L) =

d

−−→

P 0

Q

P 0 L h

Q L

P 0 Q d

R 3

R 3 −−→ P 0 Q sen ( θ ) Q d sen ( θ )

−−→

P 0

Q sen(θ)

Q d sen(θ)

h =

−−→

P

Q × d =

0

−−→

P

0

L :

x = 1 + 2t

 

y = 2 3t

 

z = 5 + 4t

t R

(2, 1, 4) L

L 1 L 2 R 3 d 1

d 2

d(L 1 , L 2 ) =| proy d 1 ×d 2

−−→ P 1 P 2

| P 1 L 1 P 2 L 2

L 1 :

x

y

z

=

=

4 + 5t

5 + 5t

= 1 4t

t R

L 2 :

x = 4 + u

y

z

= 6 + 8u

= 7 5u

u R

R 3

R 3

R 3 R 3 R 3 P ( x, y, z ) ax 2 + by

R 3 R 3 R 3 P ( x, y, z ) ax 2 + by

R 3 R 3 R 3 P ( x, y, z ) ax 2 + by

R 3 P (x, y, z) ax 2 +by 2 +cz 2 +dxy +exz +fyz